Oral Inflammations and Systemic Diseases - Aarabi, Ghazal; Seedorf, Udo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The book presents a collection of 10 articles published in a Special Issue entitled "Oral Inflammations and Systemic Diseases" in the International Journal of Molecular Sciences (ISSN 1422-0067) in the section "Molecular Pathology, Diagnostics, and Therapeutics". The oral inflammations that are covered in this issue consist of dental caries, periodontitis, and gingivitis, with a preponderance of periodontitis. Periodontitis is clearly a bacterial disease; however, it is not an infectious disease in the classical sense because it results from complex interactions between the commensal microbiota, host susceptibility and environmental factors such as diet and smoking. The human mouth contains one of the most diverse microbiomes in the human body, comprising viruses, fungi, protozoa, archaea and bacteria. The peer-reviewed articles of the book consist of original and review papers focused on the question of how exposure of the mouth to specific oral microbiota impacts systemic diseases, such as neuroinflammation, atherosclerosis, diabetes, and arthritis.